2022
DOI: 10.4258/hir.2022.28.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Standardized Curriculum for Nursing Informatics in Korea

Abstract: Objectives: This study explored the current status of nursing informatics education in South Korea and developed a standardized curriculum for it.Methods: Data were collected in two stages: first, an online survey conducted from December 2020 to February 2021 among 60 nursing schools to analyze the current status of nursing informatics education; and second, a two-round Delphi survey with 15 experts from March to April 2021 to determine the mean and standard deviation of the demand for each learning objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, previous studies have reported the inadequacy of telehealth education within nursing programs [ 43 ]. Furthermore, the undergraduate nursing informatics curriculum was reported to be insufficient, and there was scarce information on telenursing education in Korean nursing universities [ 48 ]. The lack of nursing informatics education may result in challenges for nursing students in fostering information technology competencies, potentially leading to difficulties in comprehending and utilizing telenursing.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported the inadequacy of telehealth education within nursing programs [ 43 ]. Furthermore, the undergraduate nursing informatics curriculum was reported to be insufficient, and there was scarce information on telenursing education in Korean nursing universities [ 48 ]. The lack of nursing informatics education may result in challenges for nursing students in fostering information technology competencies, potentially leading to difficulties in comprehending and utilizing telenursing.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies [13,[91][92][93][94][95][96][97][98][99][100][101][102][103] focused on determining the status of digital health and/or NI integration in undergraduate and graduate nursing curricula using mainly survey designs [92,94,95,98,99,101,103]. Four studies focused on telehealth integration [91][92][93][94].…”
Section: Studies Reporting On Status Of Curricular Integrationmentioning
confidence: 99%
“…Delphi survey [95], Internet search [96,98,101], case study [97], questionnaires [99], curriculum review [100], mixed methods examining both NI and digital health [13,102], and one study examined the status of academic EHRs utilization [103]. Variability was noted across these studies, but overall, some studies that have implemented NI or digital health have noted improvement in students' learning outcomes post integration [91,93,96,97].…”
Section: Studies Reporting On Status Of Curricular Integrationmentioning
confidence: 99%
“…Research on nursing informatics education programs includes studies such as the analysis of the status of nursing informatics education in 2000 by Park et al [37], and the development of a standard curriculum for nursing informatics in 2007 by Yom et al [38]. More recent studies include research on nursing education programs in 2016 by Jeon et al [39], and an analysis of the current status and curriculum of nursing informatics education conducted by the Nursing Informatics Special Working Group of KOSMI in 2020 [40]. An analysis of educational trends indicates an increase in undergraduate programs focused on nursing informatics [41].…”
Section: Nursing Educationmentioning
confidence: 99%